HYDRODYNAMIC ASSESMENT ON MOTION PERFORMANCE CHARACTERISTICS OF GENERIC WAVE ENERGY POINT ABSORBERS - Hernández, Lorenzo; Alzola, Jose (International Journal of Engineering Technologies and Management Research, 2017)
This work condenses various modeling techniques for different Point Absorber configurations. An alternating frequency - time domain model is implemented in MatlabFORTRAN in order to compute the displacement, velocities and the power absorbed in the heave mode for both single and multiple body configurations. Coupling of different degrees of freedom are merely contemplated with regard to a single buoy motion. NEMOH and BEMIO solvers are applied in the solution of Newtons second law according to the Boundary Element Methodology. Initially, this Wave-to-Wire model is validated through comparison with previous experimental results for a floating cone cylinder shape (Buldra-FO3). A single, generic, vertical floating cylinder is contemplated then, that responds to the action of the passing regular waves excitation. Later, two equally sized vertical floating cylinders aligned with the incident wave direction are modeled for a variable distance between the bodies. In deep water, we approximate the convolutive radiation force function term through the Prony method. Using for instance triangular or diamond shaped arrays of three and four bodies respectively, the study delves into the interaction effects for regular waves. The results highlight the most efficient layout for maximizing the energy production whilst providing important insights into their performance, revealing displacement amplification-, capture width-ratios and the commonly known park effect.